Risk Factor of Dietary Habit with Cholelithiasis - Lysandra, Annora Zerlina; Putri Wairooy, Nabilah Azzah; Ifadha, Rania Tasya; Ramainaldo S., Adra Achirultan; Albright, Ivan Angelo; Izzah, Alifah Fajriyyatul; Rahma M., Viky Nafi'ah; Lestari, Pudji (Journal of Community Medicine and Public Health Research, 2022)
Cholelithiasis affects 10-15% of the adult population. There are four main factors commonly associated with cholelithiasis abbreviated as "4F''namely female, forty, fertile and fat. However, the relationship between dietary habits as a risk factor of cholelithiasis has not been explained. The aim of the study was to determine the association between dietary habits and cholelithiasis. This study used a systematic review design with a comprehensive search of PubMed, Scopus, ScienceDirect, SpringerLink, and SAGE published from 2017 to 2021. Five studies (three prospective cohorts and two case-control studies) were included. The overall analysis of studies reported a significant risk factor of cholelithiasis in high intake of animal fats, meat, and fried foods and significant protection against cholelithiasis in high intake of fruits, nuts, fish, MUFA/SFA, n-3 FA/omega-3 fatty acids, and vegetables. Healthy dietary habits characterized by high intake in vegetables, fruits, fish, MUFA/SFA, n-3 FA/omega-3 fatty acids, and nuts will lower the risk of cholelithiasis.